Heat Transfer Analysis and Water Quality in Saline Water Desalination Using Solar Energy in Vacuum Condition - Riana Ayu Kusumadewi; Suprihanto Notodarmodjo; Qomarudin Helmy (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2018)
The continues deficiency of consumable water is a significant issue in developing countries, and contaminated water can result in various diseases, which are often lethal. Solar desalination seems to be a promising method and alternative way for supplying fresh water. Aim: The aim of this research is to study heat transfer in desalination system and the quality of feed water, distilled water and brine compared to the quality standard. Feed water consists of salinity 12‰ and 38‰ salinity. Methodology and Result: At first, initial characterization of feed water was conducted, then temperature on fourteen points was measured using thermocouples and thermometer so heat transfer rate can be calculated. After that, the final characterization of water production was conducted. From the  observation, it was found that evaporative heat transfer for vacuum pressure of -0.05, -0.1, -0.15, -0.2, -0.25, and -0.3 bar respectively were 173.77, 180.07, 190.79, 481.66, 242.57, and 246.24 W/m2. The result of water quality test of distilled water produced from saline water desalination for some parameters respectively were pH 7.4; turbidity 2.73 NTU; TDS 27.45 mg/L; chloride 84.98 mg/L; Fe 2.13 mg/L; total hardness 0.1698 mg/L; and Escherichia coli 12 cell/mL . Conclusion, significance and impact study: It can be concluded that distilled water produced by desalination system was met drinking water quality standard according to Minister of Health Regulation No. 492 of 2010.